On writing with photography - Beckman, Karen Redrobe 1971-; Weissberg, Liliane 1953- (University of Minnesota Press, 2013)
On Writing with Photography explores what happens to texts-and images-when they are brought together, addressing a wide range of genres and media, including graphic novels, children's books, photo-essays, films, diaries, newspapers, and art installations. Together, these essays help explain how writers and photographers-past and present-have served as powerful creative resources for each other.